Nghiên cứu tổng hợp, đặc trưng vật liệu Ti-MCM-48 và khảo sát khả năng xúc tác cho phản ứng oxi hóa phenol đỏ - Thành, Hồ Văn; Minh Huệ, Ngô Thị (Vietnam Journal of Chemistry, 2015)
Ti-MCM-48 material was successfully synthesized by the direct synthesis method using CTAB as a surfactant. The material characterization by XRD, BET, UV-Visible, IR and N2 adsorption showed that the titanium atoms were well dispersed in the mesoporous walls. The Ti-MCM-48 material showed a high catalytic activity in the oxidation of red phenol using H2O2. Red phenol could be oxidized almost completely into CO2 and H2O2 in a short period of time. Therefore, the Ti-MCM-48 could be considered as a potential material for treatment of organic compounds in contaminated water.